Graphene nanoribbons and nanoflakes from functionalized carbon precursors - Paiva, M. C. (2014)
The process of formation of graphene by exfoliation of carbon nanotubes (CNT) or graphite originates graphene nanoribbons (GNR) and graphene nanoflakes (GNF), respectively. These nanoparticles are expected to present interesting electronic properties, depending on their shape, size, and on their edge shape. Several methods for the unzipping of nanotubes were described in the literature [1]. The major limitations to the application of these methods are related to low yield, or to the formation of highly oxidized GNRs. The present work was motivated by the observation of the unzipping of functionalized CNT under ultra-high vacuum scanning tunneling microscopy (UHV STM) [2]. The CNTs under observation were functionalized by the 1,3-dipolar cycloaddition reaction [3], a potential route for the production of GNRs without oxidation. The formation of graphene flakes was observed when functionalized graphite was exfoliated under similar conditions as the CNT. The graphite was functionalized by the same procedure as the CNT.